Sources of medicines for hypertension and diabetes in Brazil: results from the National Health Survey - Sotero Serrate Mengue; Vera Lúcia Tierling; Noemia Urruth Leão Tavares; Andréia Turmina Fontanella (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This study aims to analyze the sources people over 18 years of age use to obtain medication for the treatment of hypertension and diabetes, according to sociodemographic characteristics from 2013 to 2019. Data from the Brazilian National Health Survey were analyzed. Most individuals with diagnosis and prescription to pharmacological treatment reported obtaining medicines exclusively from one type of source. The percentage of people who acquired hypertension medicine exclusively from public pharmacies decreased, from 24.5% in 2013 to 16.2% in 2019; while there was an increase in those obtaining from the Popular Pharmacy program, from 23.5% to 31.4%; as well as for out-of-pocket payment, which rose from 30.9% to 35.5% The percentage of people who acquired diabetes medication exclusively from public pharmacies increased from 7.4% to 18.6% and with out-of-pocket payment increased from 21.6% to 26.8%, while the percentage of those who acquired from the Popular Pharmacy program decreased from 47.2% to 36.4%. The percentage of those who acquired medication from various sources decreased for both hypertension and diabetes. For men, white, and those with higher education, the source of medication acquisition, for both conditions, was mostly by out-of-pocket payment. The high number of medicine acquisition from public sources represents an advance in Brazil's response to the treatment of these conditions, but reducing regional differences still represents a challenge to be overcome by the healthcare system.